Position statement for the management of comorbidities in psoriasis. (14th August 2018) - Dauden, E.; Blasco, A.J.; Bonanad, C.; Botella, R.; Carrascosa, J.M.; González‐Parra, E.; Jodar, E.; Joven, B.; Lázaro, P.; Olveira, A.; Quintero, J.; Rivera, R.
Abstract: Background: The association between psoriasis and some diseases has become relevant in recent years. Providing appropriate management of psoriasis from an early stage requires prompt diagnosis and treatment of concomitant diseases and to prevent any potential comorbidity. This approach should consider the adverse events of the drugs used to treat psoriasis potentially related to the onset of comorbidities. Objective: To provide the dermatologist with an accurate and friendly tool for systematizing the diagnosis of psoriasis‐associated comorbidities, which generally escapes the scope of the dermatology setting, and to facilitate decision‐making about the referral and treatment of patients with comorbidities. Methods: These position statement recommendations were developed by a working group composed of ten experts (four dermatologists, one cardiologist, one rheumatologist, one gastroenterologist, one nephrologist, one endocrinologist and one psychiatrist) and two health services researchers. The expert group selected the psoriasis comorbidities considered according to their relevance in the dermatology setting. The recommendations on diagnostic criteria are based on the current clinical practice guidelines for each of the comorbidities. The information regarding the repercussion of psoriasis medical treatments on associated comorbid diseases was obtained from the summary of product characteristics of each drug. Results: Recommendations were developed to detect and refer the following psoriasis comorbidities: psoriatic arthritis, cardiovascular risk factors (diabetes, dyslipidaemia, obesity, hypertension and metabolic syndrome), non‐alcoholic fatty liver disease, inflammatory bowel disease, kidney disease and psychological disorders (anxiety and depression). In addition, alcohol consumption and tobacco consumption were included. The tables and figures are precise, easy‐to‐use tools to systematize the diagnosis of comorbidities in patients with psoriasis and facilitate the decision‐making process regarding referral and treatment of patients with an associated disease. Conclusion: The application of these position statement recommendations will facilitate the dermatologist practice, and benefit psoriasis patients' health and quality of life.